Factors affecting Halal food purchasing by Non-Muslim / Nur Nadzirah Abd. Malek - Abd. Malek, Nur Nadzirah (Faculty of Business and Management, 2019)
The purposed of this study is to identify the factors influencing Halal food purchasing by Non-Muslim at Alor Gajah area. The model is proposed by reviewing consumer behavior theories, which is using theory of planned behavior (TPB). The research is based on a sample of 280 respondents. The results show that attitudes, subjective norms, perceived behavioral control, awareness have significant influence of Halal food purchase intention by Non-Muslim. It involve the process of conducting the research such as in determining the sample, the reliability and validity of questionnaire and including the research design, sampling technique, data collection method also involving primary data, secondary source and data analysis technique. Malaysia is a multiracial country. It is because in Malaysia consists three main religion which is Malay, Chinese and Indian. The main objective of this study is to investigate whether factors (ie: attitudes, subjective norms, perceived behavioral control, awareness) have impact on affecting of Halal food purchase intention by Non-Muslim and also to identify the most influential factor that affecting the intention of Halal food purchasing by Non-Muslim. The strongest relationship is between subjective norms and Halal food purchase intention by Non-Muslim.